Prevalence of constitutional macrothrombocytopenia in the immigrants of Northern and Eastern states of India - Hima Sree Edupuganti; Vani Krishnamurthy (Wolters Kluwer Medknow Publications, 2020)
Background: Thrombocytopenia is generally alarming to both clinicians and patients as the consequence can be disastrous. However, some of the conditions associated with thrombocytopenia can be innocuous. Unless this is recognized, detection of thrombocytopenia results in series of further investigations and management plan by clinicians. Hematological investigation in an apparently healthy/asymptomatic individual can throw up many surprises. One of them is thrombocytopenia and giant platelets on peripheral smear examination. Asymptomatic constitutional macrothrombocytopenia (also called as Harris platelet syndrome) is increasingly recognized in north and eastern parts of India. However, this condition is nearly unknown in southern part of our country. With Increased immigrants to south India from northern and eastern states, it becomes imperative for both clinicians and lab physicians to be aware of the magnitude of the condition and interpret appropriately. This can avoid unnecessary anxiety and investigations. Materials and Methods: Blood samples from 300 north and northeastern immigrants (Cases) and equal number of healthy subjects from south India (Controls) were examined for hematological parameters. Peripheral smears were examined for the presence of giant platelets. Results: Constitutional macrothrombocytopenia was seen in 4.3% of the cases and in 0.66% of the controls. The difference was statistically significant with a Fischer exact P value of 0.0067. The prevalence of macrothrombocytopenia on subjective assessment of peripheral smear was 6.7% in the cases and 1% in the control group. Conclusions: The prevalence of Harris platelet syndrome was found to be 4.3% in the immigrants from north and northeastern states.